Komposisi Jenis Hayati di Ekosistem Tambak Tumpangsari Pola Empang Parit: Studi Kasus di RPH Tegal Tangkil, BKPH Ciasem, KPH Purwakarta, Jawa Barat - Jeni Riviana; Cecep Kusmana; Agus Priyono (Jurnal Manajemen Hutan Tropika, 1999)
Biotic component composition of silvofishery using cannal-pond pattern was elucidated in this study. This pattern is the combination between fishpond canal and mangrove vegetation growing in the center.  Sampling method was conducted in the four fish ponds with different variation of mangrove vegetation composition, such as Avicennia marina monoculture, Rhizophora mucronata monoculture, regularly mixed Rhizophora mucronata and Avicennia marina, and randomly mixed Rhizophora mucronata and Avicennia marina.  The research results showed that empang parit (fish pond) having a randomly mixed R. mucronata and A. marina give the most suitable habitat for the terrestrial fauna and aquatic biota as a feeding and breeding areas.